The origins of symboling - Bednarik, Robert G. (Signs - International Journal of Semiotics, 2008)
The archaeological data traditionally utilized in considering the beginnings of symbol use by humans are described here as inadequate for this purpose. It is contended that Pleistocene finds of several types imply the use of symboling for at least several hundred millennia. Such empirical evidence includes the maritime colonization of various landmasses up to one million years ago, which is thought to demand the use of language and relatively complex technology; and the temporal distribution of first pigment use, beads and pendants, as well as engravings and proto‐figurines during the Middle Pleistocene. The introduction of iconic referrers is chronologically placed into the same period. It is argued that the cognitive evolution of hominins has been neglected in favor of less suitable indicators of humanness, such as cranial shape and perceived stone tool typology. This paper presents an alternative approach to reviewing the evolution of human cognition and symbol use.